Degradation of polycarbonate-based polyurethane via selective cleavage of carbamate and urea bonds. (November 2020) - Zhang, Hui; Cui, Xiaojing; Wang, Hongliang; Wang, Yuqi; Zhao, Yuhua; Ma, Hui; Chai, Lin; Wang, Yingxiong; Hou, Xianglin; Deng, Tiansheng
Highlights: A DES composed of choline chloride and urea was used as solvent to degrade polycarbonate-based polyurethane. The polyurethane was degraded via selective cleavage of carbamate and urea bonds with little damage on polycarbonate. The 1 H NMR shows that amino group in DES has stronger effect on carbamate bond than that on carbonate bond. High-value-added polycarbonate and o-toluidine are recovered from the waste polyurethane. Abstract: Deep eutectic solvents (DESs) have attracted broad attention due to their low cost and toxicity, easy preparation, good biological compatibility and similar characteristics to those of ionic liquids. In this study, a DES system composed of choline chloride and urea has been applied for the controllable degradation of polyurethane (PU). By the combination of Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance spectroscopy (NMR) and matrix-assisted laser analytical ionization time-of-flight mass spectrometer (MALDI-TOF-MS), the selective cleavage of carbamate and urea bonds with little damage on carbonate bonds was achieved in the DES system by the regulation of reaction conditions, which favored the recovery of both valuable polycarbonate diol (PCDL) and 3, 3′-Dimethyl-[1, 1′-biphenyl]-4, 4′-Diamine (o-toluidine). The degradation rate of PU and the yield of PCDL reached 100% and 57.4% respectively under mild conditions (1 atm, 170 °C, 8 h). A possible degradation mechanism was proposed based on the experimental results, in which the synergistic effect of choline chloride and urea activated largely the carbamate bond and thus led to a controlled degradation of PU.